Wage Posting as a Positive Selection Device: Theory and Empirical Evidence - Hermann Gartner; Christian Holzner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We use the German Job Vacancy Survey to investigate whether firms are able to attract more suitable applicants by offering bargain wages rather than posting fixed wages. Contrary to the theoretical predictions provided by the literature, we find that the offer to bargain over pay decreases the share of suitable applicants. To explain these findings we develop a directed search model with asymmetric information about workers' types and incomplete contracts, which allows firms to condition their hiring decision on the match quality revealed at the job interview. We show that wage-posting and wage-bargaining firms coexist if pooling workers with different expected match quality is too costly for wage-posting firms and if the bargaining power is not too far away from satisfying the Hosios condition. In such an equilibrium wage-posting firms hire only workers with a high match quality and wage-bargaining firms hire workers with a high and a medium match quality.
Keywords: J63; M51; J64; 330